Bridging Gaps in Theory and Practice Exploring the Value of Internship - Sinha, Sharad; Singh, Vritika (JOURNAL OF INDIAN EDUCATION, 2023)
This article examines internship in the context of teacher education. It looks into issues that need to be addressed, such as duration, implementing innovative strategies while teaching, regular feedback from school administrators, teachers and peers, reflective activities on the teaching process during internship and so on that are faced by student teachers during internships, as well as some of the ongoing practices: use of student case diary and checklist, to maintain diversity and inclusion record for school, etc., which are prevalent in some institutes and can be incorporated by others in order to improvise the internship programmes. The article also proposes measures or methods viz. identifying partner institutions, Sandwich model, etc., for addressing issues and augmenting the internship experience.